Higher-curvature gravity in AdS 3 , holographic c -theorems, and black hole microstates - Chernicoff, M. (2024)
We construct higher-derivative gravity theories in three dimensions that admit holographic -theorems and exhibit a unique maximally symmetric vacuum, at arbitrary order in the curvature. We show that these theories exhibit special properties, the most salient ones being the decoupling of ghost modes around anti–de Sitter (AdS) space, the enhancement of symmetries at linearized level, and the existence of a one-parameter generalization of the Bañados-Teitelboim-Zanelli (BTZ) black hole that, while being asymptotically AdS, is not of constant curvature but rather exhibits a curvature singularity. For such black holes, we provide a holographic derivation of their thermodynamics. This gives a microscopic picture of black hole thermodynamics for nonsupersymmetric solutions, of nonconstant curvature in higher-derivative theories of arbitrary order in the curvature.